On Convergence of the Explicit Difference Scheme for Evolution Variational Inequality with Nonlocal Space Operator - O.V. Glazyrina; M.F. Pavlova (Учёные записки Казанского университета: Серия Физико-математические науки)
Nonlinear parabolic variational inequality with a nonlocal space operator monotone with respect to the gradient is considered. Using the methods of penalty and summatory identities, explicit difference scheme with respect to the space operator and implicit difference scheme with respect to the penalty operator are constructed. Conditions of stability for the constructed difference scheme are obtained. The theorem of convergence is proved under minimal assumptions on the smoothness of the original data.